2018
DOI: 10.1016/j.isci.2018.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Marked Global DNA Hypomethylation Is Associated with Constitutive PD-L1 Expression in Melanoma

Abstract: SummaryConstitutive expression of the immune checkpoint, PD-L1, inhibits anti-tumor immune responses in cancer, although the factors involved in PD-L1 regulation are poorly understood. Here we show that loss of global DNA methylation, particularly in intergenic regions and repeat elements, is associated with constitutive (PD-L1CON), versus inducible (PD-L1IND), PD-L1 expression in melanoma cell lines. We further show this is accompanied by transcriptomic up-regulation. De novo epigenetic regulators (e.g., DNMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 53 publications
4
66
0
Order By: Relevance
“…Neural cell adhesion molecule L1 (CHL1) is frequently down‐regulated in different types of tumors, and it is verified to inhibit invasive growth and able to suppress further metastatic spread . It seems that down‐regulation of CHL1 in association with methylation change was also observed in melanoma cells by Chatterjee et al indicating that differentially methylated CHL1 is a marked alteration in melanoma cells as well.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Neural cell adhesion molecule L1 (CHL1) is frequently down‐regulated in different types of tumors, and it is verified to inhibit invasive growth and able to suppress further metastatic spread . It seems that down‐regulation of CHL1 in association with methylation change was also observed in melanoma cells by Chatterjee et al indicating that differentially methylated CHL1 is a marked alteration in melanoma cells as well.…”
Section: Discussionsupporting
confidence: 61%
“…Based on our results, methylation of EGFR gene body in correlation with up‐regulated expression was revealed in the invasive cells. Epigenetic activation of EGFR upon resistant development to BRAF inhibitors has been previously described in melanoma, as well EGFR showed methylation difference in metastatic cell lines compared with its matched primary cell lines . Recent studies indicated RBP4 serum levels as biomarker in colorectal cancer, and its overexpression was associated with ovarian cancer cell migration .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As shown in Figure 2, these trigger well-known pathways involving adaptor proteins such as TRIF, myD88, mitochondrial antiviral signaling protein (MAVS), or stimulator of IFN genes (STING) associated with the endoplasmic reticulum [30,31] to generate endogenous IFN responses. Similar upregulation of PD-L1 (CD274) in human melanoma cell lines treated by DNMTi was achieved, suggesting a possible role for DNA methylation in suppressing PD-L1 expression [23].…”
Section: Glossarymentioning
confidence: 57%
“…It was questioned whether low PD-L1 expression could be attributed to methylation of the promoter region encoding PD-L1, as prior studies in lung carcinoma have linked resistance to anti-PD1 antibody treatment with DNA methylation at the promoter region [22]. Previous analysis of the Skin Cutaneous Melanoma (SKCM) TCGA data revealed two CpG sites in the proximal promoter region encoding PD-L1, which were not methylated [23,24]. These observations suggested that a distal enhancer similar to an enhancer previously described might be involved in the epigenetic regulation of PD-L1 [25].…”
Section: Dna Methylation Status In Melanoma Tumorsmentioning
confidence: 99%